Microbiological properties and molecular profiling of microbial ecosystems during spontaneous fermentation of Carica papaya leaves: article - Abdul Khatab, Siti Norkhazwani; So’aib, Mohamad Sufian (2017)
Spontaneous fermentation has been identified that it can improve the quality of foods characteristics. It defined that this fermentation undergoes naturally without any starter culture. The microflora at the leaves in the fermentation will give the result on the unknown microorganisms present. This study is conducted to investigate the microbiological properties that present in the fermentation process. This fermentation is conducted for 100 days and this study is isolated, identified and characterized the microorganisms associated with the fermentation Carica papaya leaf on different selective media. Their biochemical characteristics have been investigated by using phenotypic characterization which is gram staining and catalase production. For further methods to know the community of the microbial, molecular profiling method has been used. The microorganisms that present in this study were genus Lactobacillus, Bacillus, Pichia, Candida, Entrobacter, Klebsiella, Cronobacter, Saccharomyces and Lactococcus. Lactobacillus plantarum is one of the Lactic Acid Bacteria and is the most frequently isolated bacteria in this study. The Bacillus genus also was detected throughout the fermentation process starting from the Day 60 until the end of the fermentation process. At the beginning of the fermentation process, Bacillus genus does not detected. This study indicates that Lactobacillus spp. is the predominant microorganisms that present in this fermentation of the Carica papaya leaves.